Soft Skills Training Strategy and Its Effect on Nurse Interns' Civil Behavior - Abeer S. Yousef; Mona M. Shazly; Heba A. Omar (Evidence-Based Nursing Research)
Contents: Soft skills are socio-emotional skills, essential for personal development and workplace success. While civility is defined as having respect for others, and it is necessary to bring attention to the importance of soft skills and civility and discuss its impact on teaching, learning, and patient outcomes.